Contemporary issues in development finance - Abor, Joshua Yindenaba; Abor, Joshua Yindenaba; Adjasi, Charles Komla; Lensink, Robert (Abingdon, Oxon : Routledge, 2021)
"Contemporary Issues in Development Finance provides a comprehensive and up to date coverage of theoretical and policy issues in development finance from both the domestic and external finance perspectives, placing emphasis on addressing the gaps in financial markets. The chapters cover topical issues including microfinance, private sector financing, aid, FDI, remittances, sovereign wealth and trade finance, as well as sectoral financing of agricultural and infrastructural projects. Readers will acquire both breadth and depth in critical and contemporary issues in development finance from a philosophical and yet pragmatic development impact approach. The text ensures this by carefully integrating the relevant theoretical underpinnings, empirical assessments and practical policy issues into its analysis. The work is designed to be fully accessible to practitioners with only a limited theoretical economic background, allowing them to deeply engage with the book as useful reference material. Readers may find more advanced information and technical details provided in clear, concise boxes throughout the text. Finally, each chapter is fully supported by a set of review questions as well as cases and examples from developing countries, particularly those in Africa. This book is a valuable resource for both development finance researchers and students taking courses in development finance, development economics, international finance, financial development policy and economic policy management. Practitioners will find the development impact, policy and conceptual analysis dimensions extremely insightful for purposes of analysing and designing intervention strategies. Joshua Yindenaba Abor is a Professor of Finance at the Department of Finance, University of Ghana Business School, Ghana. He is also a Visiting Professor of Development Finance at the University of Stellenbosch Business School, South Africa. He has made significant contributions to financial economics literature, mainly in the areas of banking and finance, development finance, financial market development, corporate finance and governance, international financial flows and growth. Charles Komla Delali Adjasi is a Professor of Development Finance and Economics at University of Stellenbosch Business School, South Africa. He is also a Visiting Professor at the Department of Economics, Econometrics and Finance, University of Groningen, Netherlands. His research focuses on financial markets development, firm productivity, international trade and household welfare. Robert Lensink is a Professor of Finance and Financial Markets at the Department of Economics, Econometrics and Finance, University of Groningen, Netherlands. He is also Professor of Finance and Development at the Development Economics Group, Wageningen University & Research, and has published widely in the area of development finance"--
Includes bibliographical references and index.
usc 27/10/2022
Keywords: Economic development; International finance; Sustainable development